Review of next generation network architecture - SHEN Qing-guo1; YU Zhen-wei1; GONG Jing2 (Tongxin xuebao)
Diversities in mobility,ambienty,trusty and virtuality of heterogenous networks lead to a lot of research and new design in network architecture.The problems and challenges of network architecture in control,security and data plane were analyzed,and some proposed solutions such as those for Internet,telecommunication and military networks were summerized.Based on the network evolution history,it is pointed that the future development direction of network architecture is to extend in the planes of control,management,security and service.The flexible application（e.g.adaptation or nesting） and smart implementation（e.g.object/service/role oriented） of layered network architecture will enrich the paradigms of networks.